Sun-simulated-driven production of high-purity methanol from carbon dioxide - Jiqing Jiao; Yanbin Ma; Xiaoqian Han; Awu Ergu; Chao Zhang; Pingping Chen; Wei Liu; Qiquan Luo; Zhaolin Shi; Han Xu; Chen Chen; Yaguang Li; et al. (Nature Communications)
Abstract CO2 conversion to CH3OH under mild conditions is of particular interest yet rather challenging. Both electro- and thermo-catalytic CO2 reduction to CH3OH can only produce CH3OH in low concentration (typically mixed with water), requiring energy-intensive purification processes. Here we design a sun-simulated-driven tandem catalytic system comprising CO2 electroreduction to syngas, and further photothermal conversion into high-purity CH3OH (volume fraction > 97%). We construct a self-supporting electrocatalyst featuring dual active sites of Ni single atoms and encapsulated Co nanoparticles, which could produce syngas with a constant H2:CO ratio of ~2 via solar-powered CO2 electroreduction. The generated syngas is subsequently fed into the photothermal module, which could produce high-purity CH3OH under 1 sun-light irradiation, with a rate of 0.238 gCH3OH gcat –1 h–1. This work demonstrates a feasible and sustainable route for directly converting CO2 into high-purity CH3OH.